PENGARUH INTELLECTUAL CAPITAL DAN KONSERVATISME AKUNTANSI TERHADAP KINERJA KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jihan Desra Fitria; Nidia Anggreni Das; Siska Yulia Defitri (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to analyze the effect of intellectual capital, accounting conservatism on financial performance with company size as a moderating variable. This research was conducted on pharmaceutical companies listed on the IDX in 2018 - 2022, the sample was selected using purposive sampling method and the data that passed the selection was 10 companies. The results showed that intellectual capital has no significant effect on financial performance while accounting conservatism has a significant effect on financial performance. In addition, company size as a moderating variable is able to moderate intellectual capital on financial performance. However, company size is not able to moderate accounting conservatism on financial performance